2008
DOI: 10.2169/internalmedicine.47.0634
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Central and Extrapontine Myelinolysis in a Case of Chronic Alcoholism without Hyponatremia: A Case Report with Analysis of Serial MR Findings

Abstract: We observed a 41-year-old woman with severe central pontine myelinolysis (CPM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 15 publications
(9 reference statements)
0
18
0
Order By: Relevance
“…These changes in serum osmolality lead to disruption of the blood-brain barrier and leakage of the hypertonic fluid into The condition can also be seen in chronic alcoholic patients unrelated to changes in the serum sodium level due to a direct toxic effect of the alcohol on the pontine fibres [34]. In alcoholic patients, extrapontine myelinolysis with involvement of the basal ganglia, thalami, deep cerebral white matter or the lateral geniculate bodies and hippocampi is exceedingly rare [35].…”
Section: Osmotic Myelinolysismentioning
confidence: 99%
“…These changes in serum osmolality lead to disruption of the blood-brain barrier and leakage of the hypertonic fluid into The condition can also be seen in chronic alcoholic patients unrelated to changes in the serum sodium level due to a direct toxic effect of the alcohol on the pontine fibres [34]. In alcoholic patients, extrapontine myelinolysis with involvement of the basal ganglia, thalami, deep cerebral white matter or the lateral geniculate bodies and hippocampi is exceedingly rare [35].…”
Section: Osmotic Myelinolysismentioning
confidence: 99%
“…Though differentiation between Graves' disease and THHG is not easy, several diagnostic clues such as past history, T3:T4 ratio is [20 and palpitations in Graves' disease helps in diagnosis of the cause of thyrotoxicosis. The CPM usually occurs due to hyponatremia [7], rapid correction of hyponatremia or chronic alcoholism [8]. But, in our case hyponatremia was corrected gradually, but the clinical features of CPM and encephalopathy improved fast with thiamine supplementation.…”
Section: Discussionmentioning
confidence: 62%
“…Reports were suggestive of hyperthyroidism with serum thyroid stimulating hormone (TSH) = 0.06 mIU/mL (0.4-5.5), total triiodothyronine (T3) = 321 pg/mL (90-200) and total thyroxine (T4) = 18 ng/mL (8)(9)(10)(11)(12)(13)(14)(15). But, T3/T4 ratio was \20:1 and hyperthyroid features were subtle leading to differential diagnosis of transient hyperthyroidism of hyperemesis gravidarum (THHG).…”
Section: Case Reportmentioning
confidence: 99%
“…But this hypothesis cannot exactly explain why many patients who have received rapid sodium correction do not develop ODS and also why patients who had mild hyponatremia slowly corrected can develop ODS (14)(15)(16) (20,21), the relative minor osmotic derangement due to the inherent lack of glucose or glycogen may predispose a person to ODS (14). Similarly (17,23,25,26), but the signal of the extrapontine lesion was variable. The extrapontine lesions related to the rapid correction of hyponatremia showed cytotoxic edema on the DWI and ADC map (23,26).…”
Section: Discussionmentioning
confidence: 99%
“…The extrapontine lesions related to the rapid correction of hyponatremia showed cytotoxic edema on the DWI and ADC map (23,26). One case report associated with alcoholics suggested that the extrapontine lesion occurred due to vasogenic edema (25) …”
Section: Discussionmentioning
confidence: 99%